Optimization Of Pai Learning Through The Problem Based Learning Method In Grade Vii Putri Islamic Boarding School Modern Daarul Muttaqien 2 Tangerang - Susiana, Meilia; Tis'ah, J. Anhar Rabi Hamsah; Mujakir, H. (Universitas Pakuan, 2025)
This research is motivated by the importance of improving the quality of Islamic Religious Education (PAI) learning so that it is not only oriented toward knowledge but also able to foster students’ critical thinking, creativity, and collaborative skills. The purpose of this study is to optimize Islamic Religious Education learning through the Problem Based Learning (PBL) method. The research method used is a qualitative approach, with data collected through observation, interviews, and documentation involving PAI teachers, student affairs teachers, and seventh-grade female students at Pesantren Modern Daarul Muttaqien 2 Tangerang. The results of the study show effective outcomes, where the PAI teacher successfully created a more active, collaborative, and contextual learning environment. The implementation of the Problem Based Learning method helps students understand religious material through an approach focused on solving problems relevant to their daily lives, making the learning process more meaningful and engaging. The teacher acts as a facilitator who guides students in finding solutions to problems related to the subject matter, thereby making learning more meaningful. The application of Problem-Based Learning in PAI for seventh-grade female students has proven to enhance the quality of the learning process while providing a more contextual and in-depth learning experience, in line with the objectives of Islamic education in pesantren.